2018
DOI: 10.1007/s13668-018-0228-z
|View full text |Cite
|
Sign up to set email alerts
|

Stevia rebaudiana Bertoni and Its Effects in Human Disease: Emphasizing Its Role in Inflammation, Atherosclerosis and Metabolic Syndrome

Abstract: A growing body of evidence indicates that Stevia rebaudiana Bertoni is protective against malignant conversion by inhibition of DNA replication in human cancer cell growth in vitro. Consumption of Stevia has demonstrated to be generally safe in most reports. Further clinical studies are warranted to determine if regular consumption brings sustained benefits for human health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 92 publications
0
16
0
1
Order By: Relevance
“…Studies have shown that compounds found in stevia are not teratogenic, mutagenic, or carcinogenic and cause no acute or subacute toxicity . Moreover, reports have been promising regarding the potential benefits of stevia against inflammation, carcinogenesis, atherosclerosis glucose control, and hypertension . Interestingly, based on the present data, it might be reasonable to postulate that stevia is a potential natural plant to treat patients with liver disorders.…”
Section: Discussionmentioning
confidence: 63%
“…Studies have shown that compounds found in stevia are not teratogenic, mutagenic, or carcinogenic and cause no acute or subacute toxicity . Moreover, reports have been promising regarding the potential benefits of stevia against inflammation, carcinogenesis, atherosclerosis glucose control, and hypertension . Interestingly, based on the present data, it might be reasonable to postulate that stevia is a potential natural plant to treat patients with liver disorders.…”
Section: Discussionmentioning
confidence: 63%
“…With increased consumer interest in reducing sugar intake, food products made with sweeteners rather than sugar have become more popular [42]. Additionally, consumption of stevia has demonstrated to be generally safe in most reports [43].…”
Section: Discussionmentioning
confidence: 99%
“…The chemical structure of steviol glycoside present as an aglycone (steviol) and three molecules of glucose (Chatsudthipong and Muanprasat 2009). To date, at least 12 steviol glycosides have been identified from stevia leaves, which one of the best-known being stevioside (Rojas et al 2018). Other steviol glycosides are rebaudioside (A-F), steviolbioside and dulcoside A (Shibata et al 1995;Rojas et al 2018).…”
Section: Chemical Constituent and Extraction Of The Bioactive Compounmentioning
confidence: 99%
“…To date, at least 12 steviol glycosides have been identified from stevia leaves, which one of the best-known being stevioside (Rojas et al 2018). Other steviol glycosides are rebaudioside (A-F), steviolbioside and dulcoside A (Shibata et al 1995;Rojas et al 2018). As cultivation conditions may affect the content of glycosides in stevia leaves, the yield of steviosides and rebaudioside A can from 16.3-95 mg/g and 6.86-44.1 mg/g of dry leaves weight, respectively (Wood et al 1955).…”
Section: Chemical Constituent and Extraction Of The Bioactive Compounmentioning
confidence: 99%